Shortening the Leuven perceptual organisation screening test with item response theory and confirmatory factor analysis - Vancleef, K; Demeyere, N; Sun, L (Center for Open Science, 2021)
The Leuven Perceptual Organisation Screening Test (L-POST) is a reliable and validated test for mid-level visual perceptual deficits after brain injury. However, the test’s duration (20-35 minutes) is too long for a screening approach for all patients in clinic practice. Our aim was to shorten L-POST to 10-15 minutes based on statistical criteria of the items. We collected a sample of 3391 participants who completed L-POST. The test consists of 15 subtests with 5 items each. First, we demonstrated high internal consistency of the subtest items through Cronbach’s alpha and observed high correlations between scores based on all five items versus a selection of only two items per subtest. This showed that two items per subtest are sufficient. Next, Item Response Theory (IRT) was applied to guide the selection of the items. The highest correlation with full-scale subtest scores was observed when two items were selected following an adaptive testing procedure. A pilot validation in a subsample of participants with low abilities demonstrated adaptive testing has reasonable sensitivity (79%) but limited specificity (54%) in classifying participants with impaired and unimpaired abilities. Last, we reduced the number of subtests through factor analysis. We showed that the subtests using Radial Frequency Patterns as stimuli were redundant and could be combined in one subtest. We conclude that L-POST can be shortened to 26 items (7-14 minutes) and when used with fixed items could prove particularly useful for screening purposes.